Plan de negocio para la creación de un centro de acopio de cacao en el cantón Montalvo, provincia de Los Ríos. - Estrella Paredes, Gilo Raúl (2022)
The present work called Business Plan for the creation of a cocoa collection center in the Montalvo canton, Los Ríos province, had the objective of determining the feasibility of the cocoa collection center in the Montalvo canton, Los Ríos province, as well as argue theoretically the main concepts and elements that influence the creation of a cocoa collection center. To conduct a market study to identify the unsatisfied demand and the main requirements; in addition to developing the technical, administrative, financial and legal study to determine the feasibility of the collection center. In the methodological part, this research work has a quantitative design, since this type of research increases, the contingency of developing the extensions of an exploration project, and the sense of scope is greater and deeper, complemented with the types of exploratory and descriptive research. As a research method, the empirical method will be used, this method is based on the experience of real contact; for this research study, the cocoa farmers of Montalvo canton and its surrounding places are considered as a population; however, the representatives of the cocoa marketing companies that are located in places near Montalvo canton will also be taken into account. The results obtained suggest its implementation because the NPV and IRR calculations establish that there will be a growth of $ 11,587.94 and a rate of return of 16%, with a benefit cost of 0.14 cents for each sale, giving road to the project of creating the Estrella Collection Center in the Montalvo canton.